MILLIY URF–ODATLAR VA TURIZMNI RIVOJLANTIRISHDA TURISTIK MARSHRUT ISHLAB CHIQISHDA XIZMATLAR KO‘RSATISH TALABIA.Abdullaev – tarix fanlari bo‘yicha falsafa doktori, dotsent - Ermanov, A.; Erimbetov, E. (SCIENCE and SOCIETY, 2023)
In this article, we will see that there are almost no historians, literary critics and people interested in ethno-ethnographic tourism, and there is no need to develop a separate direction. According to the article, ethnographic tourists can easily move from one destination or place to another by hiring an interpreter, guide and mode of transport.